Pengembangan Media Pembelajaran Catur Belajar Untuk Meningkatkan Pemahaman Siswa Pada Pembelajaran IPS Sekolah Dasar - Siti Aisah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to describe the feasibility of learning chess media in the implementation of learning and to describe the effectiveness of learning chess media in increasing students' understanding of elementary school social studies material. The research method used is the Research and Development Borg and Gall model which was adapted from Sugiyono. The research subjects were the 4th grade students of SDN Sukamurni, totaling 10-12 people. Methods of data collection using questionnaires and tests, while the data analysis technique uses product data analysis and effectiveness analysis. The results showed that there were 70% of students who had grades at ≥ 80 or about 70% of the 20 students. The remaining six students who have a score of  ≤ 60. Before the use of chess media learning in the learning process. After the use of learning chess media in the implementation of learning, there are 17 students or about 85% who get a score of  ≥ 80. The remaining 3 students get a score of ≤ 60.